Effect of Type of Irrigation System on Productivity and Income of Date Palm Growers in Sebha, Libya - Aridah, Ahmad Mohamed Ahmad (Curtin University, 2016)
This research examines the variables affecting the production of date palm, the fruit quality of common varieties of dates, and the income of date palm farmers in Sebha, Libya. It provides new insights into factors that affect the technical efficiency of date palm production, and the physical and chemical characterises of dates. The research shows the pros and cons of different types of irrigation systems and outlines important policy implications for irrigation in Libya.